Thomas Mann und die beiden totalitären Diskurse des Judentums: Überlegungen zu seinen publizistischen Schriften (1907-1933) - Kodjio Nenguié, Pierre (Revista de Filología Alemana, 2007)
It is obvious that the jew related totalitarisms (zionism and antisemitism) are writing categories in the work of Thomas Mann. A proof of this is the Berliner Colloquium of 2002 with the title “Thomas Mann und das Judentum”. As writing categories it both totalitarian discourses can not only be exemplified and illustrated trough his essays, but also in his poetic work. They comprise statements that can be helpful to understand his main ideas on “the Jewish” related totalitarian discourses. The following contribution can be understood as a sort of continuation of Berliner Colloquium, but limits at the essays between 1907 and 1933. An attention is paid to his attitudes to antisemitism and sionism, but totalitarian discourses. Therefore, Thomas Mann criticises both ideologies while apologising for a peaceful, humanatarian and intercultural order.